STRATEGI PENGEMBANGAN KEMAMPUAN ANAK AUTISME SECARA TERPADU - Gustini, Susi; Istiyanti, Istiyanti (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2009)
Autism or autistic disorder is often called autism or autistic (childhood autism, infantile autism or early infantile autism), is a pervasive developmental disorder, occurs in children before age 3 years. Disorders are marked by disruptions in social interaction and communication patterns of behavior that sterotipik limited. The presence of autistic children in a family needs to be understood properly. Should be explained to parents and families that are not autistic child means a child will not grow again, but should also be explained that although there will be development and progress, children will not reach the level like normal children the same age. Action that needs to be done is to educate and train in accordance with the level of development disorders. Education and training can be provided in the classroom or in the open space that can provide protection to the child and at the same time can also provide an opportunity for him to be optimistic in accordance with the conditions of his ability. Education and training should be referred to by a team consisting of various professions and involve parents.